BUDAYA BELANJA MAKANAN DAN MINUMAN MASYARAKAT KOTA TANJUNGPINANG DI MASA PASCA PANDEMI (STUDI KASUS FITUR GOFOOD PADA APLIKASI GOJEK) - Selvi Fauzar; Dwi Septi Hariyani; Anisa; Septa Diana Nabella (LPPM Universitas Ibnu Sina, 2022)
This study aims to determine whether the Gofood feature on the Gojek application affects the food and beverage shopping culture of the people of Tanjungpinang City in the post-pandemic period. The method used in this study is a quantitative method. Data collection techniques were carried out in two ways, namely library research and distributing questionnaires. The population in this study is the people of Tanjungpinang city with a total sample of 30 respondents. The research data were collected and processed using Microsoft excel and presented in the results and discussion section. The result of this study is that the trend of shopping for food and beverages is slowly starting to shift along with the covid 19 pandemic. If previously people liked to shop for food and drinks by coming directly to the store, now most of them are starting to use the Gofood feature on the Gojek application because they feel it is more convenient. easy, simple, and fast.